Global change and climate‐driven invasion of the Pacific oyster (Crassostrea gigas) along European coasts: a bioenergetics modelling approach. (4th November 2015) - Thomas, Yoann; Pouvreau, Stéphane; Alunno‐Bruscia, Marianne; Barillé, Laurent; Gohin, Francis; Bryère, Philippe; Gernez, Pierre
Abstract: Aim: The spread of non‐indigenous species in marine ecosystems world‐wide is one of today's most serious environmental concerns. Using mechanistic modelling, we investigated how global change relates to the invasion of European coasts by a non‐native marine invertebrate, the Pacific oyster Crassostrea gigas . Location: Bourgneuf Bay on the French Atlantic coast was considered as the northern boundary of C. gigas expansion at the time of its introduction to Europe in the 1970s. From this latitudinal reference, variations in the spatial distribution of the C. gigas reproductive niche were analysed along the north‐western European coast from Gibraltar to Norway. Methods: The effects of environmental variations on C. gigas physiology and phenology were studied using a bioenergetics model based on Dynamic Energy Budget theory. The model was forced with environmental time series including in situ phytoplankton data, and satellite data of sea surface temperature and suspended particulate matter concentration. Results: Simulation outputs were successfully validated against in situ oyster growth data. In Bourgneuf Bay, the rise in seawater temperature and phytoplankton concentration has increased C. gigas reproductive effort and led to precocious spawning periods since the 1960s. At the European scale, seawater temperature increase caused a drastic northward shift (1400 km within 30 years) in the C. gigas reproductive niche and optimal thermal conditions for early life stage development. Main conclusions: We demonstrated that the poleward expansion of the invasive species C. gigas is related to global warming and increase in phytoplankton abundance. The combination of mechanistic bioenergetics modelling with in situ and satellite environmental data is a valuable framework for ecosystem studies. It offers a generic approach to analyse historical geographical shifts and to predict the biogeographical changes expected to occur in a climate‐changing world.